Clinical features, laboratory profile and outcomes among dengue patients admitted in a tertiary care hospital, Delhi NCR - Tiwari, Mohit; Tibrewal, Abhishek; Pichika, Varun S. (International Journal Of Community Medicine And Public Health, 2020)
Background: Globally, dengue, a mosquito-borne viral infection, is the most rapidly spreading vector-borne disease. Dengue fever is endemic in >100 countries including India. Dengue has a variety of clinical presentations. The objective of the study was to understand the clinical features, laboratory profile and outcomes of dengue fever among patients admitted in a tertiary care hospital in Delhi, National Capital Region. Methods: This was a cross-sectional study among 75 dengue confirmed (NS-1 antigen and/or IgM antibody positive) patients with fever <1 week. The variables included were socio-demographic; clinical features; laboratory and radiological profile and outcomes. Descriptive analysis was used. Results: The majority of the patients were aged between 18-40 years 72% and predominantly males 68%. A total of 18.7% patients (malaria: 13.3% and chikungunya: 5.3%) had co-infection. Fever was present in all the patients, followed by myalgia (74.7% patients), retro-orbital pain/headache 69.3%, and vomiting 45.3%. The mean hemoglobin was 13.9 gm/dl, leukopenia 46.7% patients, thrombocytopenia 96.0% and elevated liver enzymes 69.3%. Radiological examination showed pleural effusion 6.7%, gallbladder wall thickening 6.7%, splenomegaly 4.0%, and hepatomegaly 2.7%. The outcomes included ICU care 17.3%, ventilator support 13.3%, blood transfusion 14.7%, and mortality 1.3% during the hospital stay. Conclusions: Dengue has become a major public health problem in India. The most common clinical features are fever, myalgia, headache and vomiting; laboratory abnormalities are leukopenia, thrombocytopenia and deranged liver enzymes. No specific treatment exists, but early detection and proper medical care lowers fatality rates.